A leitura de infográficos sob à luz dos multiletramentos e da abordagem multimodal - Rolim, Leiliany Aparecida de Souza (2025)
The increasing use of multimodal texts in textbooks reflects the transformations in reading and interpretation practices in contemporary reading. Among these texts, infographics stand out by integrating verbal and visual elements in a complementary manner, presenting information dynamically and accessibly. This research investigated how infographics in a Portuguese Language textbook for high school articulate and incorporate semiotic resources through a multimodal approach, in addition to analyzing their potential for fostering multiliteracies. The methodology adopted was bibliographic and qualitative, based on the analysis of the textbook’s infographics, with a focus on the interaction among the semiotic elements of the composition reading how these texts were embedded within the material. To this end, the study was grounded in the works of authors such as Paiva (2009, 2013, 2021), Gualberto and Santos (2019), and Kress and van Leeuwen (2021) through the Visual Design Grammar (GDV). The GDV provided tools that enabled the analysis of compositional aspects such as the value of information, salience, use of colors, typography, framing, layout, and visual rhyme in the infographics. The results indicate that, despite the multimodal structure of the infographics, their pedagogical exploitation is limited. Many infographics are not integrated into the chapter activities and, in some cases, appear solely as a summary reading or thematic resource, without effectively promoting critical reading and the practice of multiliteracy pedagogical movements. Furthermore, the reduced number of infographics in the analyzed material contrasts with their relevance for developing multimodal reading skills. In conclusion, there is a need for a more effective pedagogical approach that values the integrated reading of multimodal texts and makes greater use of infographics as teaching tools. This research contributes to studies on multimodality and multiliteracies by highlighting gaps in the exploitation of these resources in the analyzed textbook